Design and Simulated Characteristics of Nanosized InSb Based Heterostructure Devices - T. D. Subash; T. Gnanasekaran; C. Divya; J. Jagannathan (Advances in Materials Science and Engineering)
Indium antimonide nanoparticles were synthesized at room temperature. X-ray diffraction measurements are utilized to characterize the nanocomposites. The InSb nanoparticle has an average particle size in a range of 47 mm to 99 mm which is observed using the XRD result. The InSb is a material which is used to design the transistor. For designing purpose the simulator TCAD is used, by which the HEMT device is structured and its performance is analyzed and it is found that transistor operates as normal devices. This designed device is more valuable since a nanocomposite InSb material is used as a channel in HEMT device, thereby leading to the nanosized HEMT device. In addition, InSb has the property of high saturation velocity and mobility which results in higher performance of the device than any other materials in III-V compounds.